Demography, growth and robots in advanced and emerging economies - Matteo Lanzafame (Economics and Econometrics Research Institute (EERI), 2022)
This paper provides estimates of the impact of demographic change on labor productivity growth, relying on annual data over 1961-2018 for a panel of 90 advanced and emerging economies. We find that increases in both the young and old population shares have significantly negative effects on labor productivity growth, working via various channels - including physical and human capital accumulation. Splitting the analysis for advanced and emerging economies shows that population ageing has a greater effect on emerging economies than on advanced economies. Extending the benchmark model to include a proxy for the robotization of production, we find evidence indicating that automation reduces the negative effects of unfavorable demographic change - in particular, population aging - on labor productivity growth.
Keywords: C33; J11; O40; 330; Demographic change; labor productivity; robots